Introducing Price Signals into Land Use Planning Decision-making - a Proposal - Paul Cheshire; Stephen Sheppard (European Regional Science Association (ERSA), 2005)
Although directed to the British system of land use planning this paper has relevance for many OECD countries. The paper starts by characterising the basic features of planning systems which seek to impose 'growth boundaries' as has been the case in Britain since 1947. In contrast to the planning literature this analyses such policies as an issue of resource allocation. A conclusion is that the system explicitly excludes any use of price signals from its decisions and effectively determines the supply of land for any use by fiat. Cumulatively over time the result has been to generate major distortions in land market prices. Because the planning system has deliberately constrained the supply of space, and space is an attribute of housing which is income elastic in demand, rising incomes not only drive rising real house prices but also mean that land prices have risen considerably faster than house prices. Several housing attributes other than garden space are to a degree substitutes for land but the underlying cause of the inelastic supply of housing in the UK is the constraint on land supply. The final section proposes a way of including the information embodied in the price premiums of neighbouring parcels of land zoned for different uses in determining land supply while safeguarding the underlying purposes of land use regulation. Such premiums signal the relative scarcity of land for different uses at each location and should become a key element in planning decision-making. If they were above some threshold, this should provide a presumption of development unless maintaining the land in its current use could be shown to be in the public interest. If combined with Impact Fees, such a change would not only make housing supply more elastic and the system more transparent but would help to distance land availability decisions from the political process.
Keywords: 330